SOME RESULTS OF TEN YEAR OPERATION OF THE AUTOMATIC MEASURING COMPLEXES PARSEC - Sergeeva, T. P.; Sergeev, A. V. (Одеські астрономічні публікації, 2017)
The brief description of the automatic measuring complexes PARSEC and some results of their ten years operation have been reported in the paper.